2016
DOI: 10.1074/jbc.m116.740597
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Myocyte-specific Knock-out of Calcium-independent Phospholipase A2γ (iPLA2γ) Decreases Oxidized Fatty Acids during Ischemia/Reperfusion and Reduces Infarct Size

Abstract: Calcium-independent phospholipase A 2 ␥ (iPLA 2 ␥) is a mitochondrial enzyme that produces lipid second messengers that facilitate opening of the mitochondrial permeability transition pore (mPTP) and contribute to the production of oxidized fatty acids in myocardium. To specifically identify the roles of iPLA 2 ␥ in cardiac myocytes, we generated cardiac myocyte-specific iPLA 2 ␥ knock-out (CMiPLA 2 ␥KO) mice by removing the exon encoding the active site serine (Ser-477). Hearts of CMiPLA 2 ␥KO mice exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 60 publications
(73 reference statements)
1
27
0
Order By: Relevance
“…Consistent with this notion, our recent findings have demonstrated that murine myocardial mitochondrial iPLA 2 ␥ is activated by calcium and that iPLA 2 ␥ loss of function in cardiac myocytes markedly attenuates Ca 2ϩ -induced mPTP opening, generation of proinflammatory oxidized lipid metabolites (e.g. eicosanoids, docosanoids, and oxidized linoleic acid metabolites), and membrane potential dissipation resulting in reduction of infarct size during cardiac I/R in mice (13,27). ** ** * Figure 5.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Consistent with this notion, our recent findings have demonstrated that murine myocardial mitochondrial iPLA 2 ␥ is activated by calcium and that iPLA 2 ␥ loss of function in cardiac myocytes markedly attenuates Ca 2ϩ -induced mPTP opening, generation of proinflammatory oxidized lipid metabolites (e.g. eicosanoids, docosanoids, and oxidized linoleic acid metabolites), and membrane potential dissipation resulting in reduction of infarct size during cardiac I/R in mice (13,27). ** ** * Figure 5.…”
Section: Discussionsupporting
confidence: 67%
“…Through sequential chromatographies in conjunction with activity-based protein profiling and high mass accuracy proteomics (45, 46), we quite unexpectedly identified the predominant phospholipase activity associated with nonfailing human heart mitochondria as cPLA 2 . In stark contrast, the predominant mitochondrial phospholipase activity in failing hearts was catalyzed by iPLA 2 ␥ generating toxic HETEs which, in combination with a prominent decrease in protective EETs, likely results in alterations in surface charge and potential in the mitochondrial membrane (27,47). Moreover, previous studies by our group reported the regiospecific PLA 1 activity of iPLA 2 ␥ with phospholipids containing polyunsaturated fatty acids at the sn-2 position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the prolonged opening of mPTP has been implicated in mitochondrial swelling, cytochrome c release, and necrotic cell death; however, the precise mechanism mediating mPTP opening is incompletely understood (1,2). A series of investigations by Gross and colleagues have also pointed to a role for the mitochondrial phospholipase isoform iPLA 2 ␥ in these pathological processes (3)(4)(5)(6). This enzyme cleaves one of the carbon chains from phospholipids to release the fatty acid arachidonic acid (AA), which can be oxidized into signaling-active eicosanoids.…”
mentioning
confidence: 99%